Providing Equivalent Learning Activities with Software-Based Remote Access Laboratories - Kist, Alexander A.; Basnet, Badri (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Laboratory-based learning activities are important components of engineering and surveying education and it is difficult to offering practical activities to distance education students. Remote Access Laboratory (RAL) systems are widely discussed as learning tools to offer students remote access to rigs or hardware. In some disciplines laboratory activities are purely software based and RAL systems can be used to provide access to software. As part of a larger study into the transferability of the remote laboratory concept to non-engineering disciplines this project evaluates the effectiveness of RAL based software activities in supporting student learning is investigated. In the discipline of Surveying and Spatial Science, RAL technology is used to provide Geographic Information System software access to distance students. The key research question discussed in this paper is whether RAL-based software activities can address the same learning outcomes as face-to-face practical classes for software activities. Data was collected from studentsâ?? discussion forums, teaching staff diaries and teaching staff interviews. The project demonstrates that students undertaking learning activities remotely achieve similar learning outcomes than student in practice classes using the same software. Ease of system access and usability are critical and the learning activity needs to be supported by comprehensive learning materials. This research provides a clear case in which the use of RAL technology has provided inclusive educational opportunities more efficiently and these general results are also applicable to experiments that involve physical hardware.